2009
DOI: 10.5194/acp-9-2195-2009
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of cloud lifecycles in cloud-resolving models

Abstract: Abstract.A new technique is described for the analysis of cloud-resolving model simulations, which allows one to investigate the statistics of the lifecycles of cumulus clouds. Clouds are tracked from timestep to timestep within the model run. This allows for a very simple method of tracking, but one which is both comprehensive and robust. An approach for handling cloud splits and mergers is described which allows clouds with simple and complicated time histories to be compared within a single framework. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Many others have tracked clouds in models [11][12][13]28], from radar data [9,10], or from photography [38]. Most of these previously employed methods share computational and conceptual characteristics with one another and with the method we discuss below.…”
Section: Cloud Trackingmentioning
confidence: 99%
See 3 more Smart Citations
“…Many others have tracked clouds in models [11][12][13]28], from radar data [9,10], or from photography [38]. Most of these previously employed methods share computational and conceptual characteristics with one another and with the method we discuss below.…”
Section: Cloud Trackingmentioning
confidence: 99%
“…Additionally, 6% of clouds split and then remerge at some later time. Similarly, Plant [28] and Lochbihler et al [63] found that approximately half of all convective events are associated with a split or merger but Dawe and Austin [13] found far fewer shallow clouds are. Convection is clustered in the RCE simulation in which clouds are tracked so it is impossible to know whether this split/merger frequency represents a natural one.…”
Section: Splits and Mergersmentioning
confidence: 99%
See 2 more Smart Citations
“…It opens a possible route towards statistical cumulus dynamics, a methodology proposed by Arakawa and Schubert (1974) as a systematic approach to the closure problem. At present, only semi-phenomenological descriptions of some aspects of equilibrium statistical cumulus dynamics exist (e.g., Craig, 2004, 2006;Craig and Cohen, 2006;Plant and Craig, 2008;Plant, 2009). In order to address time-varying applications, such investigations should also be compared with suitable CRM analyses of plume statistics, such as those produced by Xu and Randall (2001).…”
Section: Discussionmentioning
confidence: 99%